Paradara Dalam Delik Kesusilaan Di Kota Denpasar: Persepektif Hukum Hindu - I Nyoman Alit Putrawan; I Nyoman Sirta; I Gusti Ngurah Sudiana (Jayapangus Press, 2019)
Crimes against women (paradara) often occured in people's lives. Moral degradation and decency as one of the opposite causes, the victims were Hindu women, such as rape, adultery, sexual abuse and child copulation. Hindu women used the object of abuse for the perpetrators of paradara. Paradara and dispute laws were laws that could be accepted according to the provisions of the Criminal Code and also the provisions of Law No. 23 of 2002 and Law No. I7 of 2016 concerning the protection of children with a maximum prison sentence of 20 years. Paradara and following the moral dispute, which took place in the city of Denpasar, carried out by individuals or groups of people in connection with Hindu women were seen as being weak and easily harassed by supporters. Women in Hinduism were very respected and also honored, because Hindu women who gave birth succeeded in winning the continuity of Hinduism. Once approved, the woman would receive prosperity and where women were harassed then the misery and destruction would be obtained. If there was a crime, Paradara applied Hindu law as a death sentence, the purpose of the application of punishment is to provide peace and harmony